Pengaruh Budaya Organisasi dan Pelatihan terhadap Kinerja Karyawan - Rizky Putra Akbar; Ratnawaty Marginingsih (Lembaga Pengembangan Kinerja Dosen, 2024)
The Office of the Ministry of Religious Affairs in Bogor Regency continues to strive to improve its performance and services. One of the efforts made is through a work training program for employees. The purpose of this research is to determine the influence of organizational culture and work training on employee performance. The research method used is a quantitative approach with data collection techniques using saturated samples or non-probability sampling, where the entire population is used as a sample. The population in question includes all employees of the personnel division of the Office of the Ministry of Religious Affairs in Bogor Regency, totaling 52 respondents, using a questionnaire measured on a Likert scale. In processing the data for analysis using SPSS 26 software with multiple linear analysis techniques, the research results showed that Y = 4.434, X1 = 0.402, and X2 = 0.361, which includes instrument tests, classical assumption tests, partial hypothesis tests with T values of 3.560 for X1 and 3.325 for X2. Simultaneously, both independent variables obtained an F value of 18.588. The coefficient of determination test indicated that the two independent variables have a 43.1% influence on employee performance